Research on the Connection and Conflict between Civil Law and Criminal Law in Property Protection - Zhang, Guoqi (International Journal of Social Sciences and Public Administration, 2025)
This article aims to explore the connection and conflict between civil law and criminal law in property protection. With the continuous deepening of the construction of the rule of law in China, the legal system is becoming more and more perfect. However, in practice, civil law and criminal law often conflict on property protection, which brings certain troubles to judicial practice. Through the analysis of the legislative purpose, adjustment object and legal effect of civil law and criminal law in property protection, this article reveals the causes and manifestations of legal conflicts, and puts forward suggestions to resolve conflicts. The study found that improving legislation and improving the level of judicial practice is the key to reducing legal conflicts and maintaining the unity of the rule of law.